An investigation of practitioner and parent causal attributions for perceived challenging behaviour in Early Years Foundation Stage - Geoghegan, Rheanna (2022)
Challenging behaviour in schools is a widely discussed topic, with an array of negative impacts identified for pupils, staff, and parents. Research indicates that the attributions held by key adults can impact the support that they give to young people exhibiting these behaviours, including their interactions, relationships, behaviour management, and intervention implementation (Försterling, 2001). Attributions for challenging behaviour have previously been explored for primary and secondary age pupils (Lambert & Miller, 2010; Miller, 1995; Miller et al., 2002). However, staff and parent attributions in relation to Early Years have not been specifically researched. It has been identified that there may be differences in attributions for behaviour in younger children compared with older children (Dix et al., 1986; Johnston, Patenaude, & Inman, 1992; Phares, Ehrbar, & Lum, 1996). The present study aims to explore parent and practitioner causal attributions for challenging behaviour relating to children aged 3-5 years old, in the context of Early Years Foundation Stage (EYFS).